Isolation, Identification and Biological Assay of coriander oil fromcoriandrum sativum as antibiotic - Abd-Mohsen, Wisal; Al-Swdanii, Zaid (Iraqi Journal of Science, 2025)
This study is designed to extract and identify the essential coriander oil from Coriandrum sativum. The Antimicrobial activity of Coriander oil was studied in various microorganisms (Staphylococcus aureus, Klebsiella pneumonia, Streptococcus pyogenes, Candida albicans, Eschirichia coli, Pseudomonas aeroginosa and Proteus vulgaris) using inhibition zone method (Aromatogram). The Extraction process is carried out by steam distillation. Optimum organic extractant determined. The collected oil is identified via Thin Layer Chromatography (TLC) using a mixture of Ethylacetate : Tolune (1:9) as a mobile phase. The MIC for each microbes were estimated.